MARINE FISHERIES AND ITS IMPACT ON COMMUNITY: AN OVERVIEW - MAHBOOB, K; SHAHZAD, SM (Biological and Clinical Sciences Research Journal, 2024)
Marine Fishery is the harvesting of fish and other seafood from the ocean for commercial, recreational, and food purposes. Marine fisheries, resources provide animal proteins to billions of people globally. Marine fishery has a vital role in human development and welfare as it provides employment, production, and trade, and has a significant share. In the national economy. There are several types of marine fisheries, which provide food security, livelihoods and economic benefits to millions of people especially the coastal communities. Sustainable fisheries of the world, facing many problems, like overfishing, habitat destruction, and climate change resulted in the depletion of fish stock and threat to the marine ecosystem. To get the long- term benefits and to reduce the pressure on marine fishery, conservation efforts i.e. sustainable fishing, marine protected areas establishment and enhancing aquaculture productivity are essential. Coastal area communities around the world usually depend upon the fishing industry for their food, income, and livelihood. Marine fisheries impacted on the communities in both ways i.e. positively and negatively. Economic and ecological impacts of marine fisheries on communities are significant. To mitigate negative impacts and enhance positive impacts of marine fisheries on the communities, the present project is undertaken to highlight those impacts by gathering the data about marine fisheries and its allied subjects from 1980 - 2024. In the end some suggestions are coated, like fisheries management practices, community-based management, and social responsibility initiatives, for better and sustainable fishery industry of the country.